PICASSO : exploratory search of connected subgraph substructures in graph databases - Bhowmick, Sourav Saha (2019)
Recently, exploratory search has received much attention in information retrieval and database fields. This search paradigm assists users who do not have a clear search intent and are unfamiliar with the underlying data space. Specifically , query formulation evolves iteratively as the user becomes more familiar with the content. Despite its growing importance, exploratory search on graph-structured data has received little attention in the literature. We demonstrate a system called picasso to realize exploratory sub-structure search on a graph database containing a set of small or medium-sized data graphs. picasso embodies several novel features such as progressive (i.e., iterative) formulation of queries visually and incremental processing, multi-stream results exploration wall to visualize, explore, and analyze search results to identify possible search directions.